LINGUISTIC CONCEPTUALIZATION OF SPATIAL PREPOSITIONS: ROMANIAN ‟ÎN” AND POLISH ‟W” ‒ A COMPARATIVE APPROACH - OCZKO, Anna (Studia Universitatis Babeș-Bolyai Philologia, 2023)
Linguistic Conceptualization of Spatial Prepositions: Romanian “în” and Polish “w” – Comparative Approach. The Romanian preposition "în" corresponds to the Polish preposition "w". Both express the spatial relationship that consists of placing an object in a limited space; they indicate the interior of the space where something is located. In addition to this general definition in both languages, the preposition acquires other semantic functions that may be convergent, rendered directly by the pair Rom. în = Pol. w. Furthermore, representation of some linguistic relations can be different: for a Romanian speaker, the space relation could be reflected by preposition representing a closed space – în, but for a Polish speaker, it reflects an open space or a surface coralated to the Polish preposition – na. The main objective of this article is to analyze the differences that, first, result from the distinctive conceptualization of space reflected in the language using prepositions and, secondly, result from heterogenous grammatical system (Roman vs. Slavic). The analysis is based, among other things, on the frequent mistakes in the use of prepositional structures that Polish speakers make when learning Romanian. The wrong structures appear especially at the level of abstract language, in phrases or verbs, when the regime imposes prepositions or cases that do not correspond functionally to the native ones; however, the linguistic image of the space is also different and difficult to identify in the metaphorical or abstract structures. The cognitive approach allows the delineation of some image schemes that represent the core meaning of the preposition. The comparative study of the preposition in the Romanian and Polish languages shows that the prepositional system in the Romanian language is more developed and richer than the Polish one, and the latter presents a much stronger and more direct attachment to the feature of "interiority" expressed by the preposition "w / în" than in the Romanian language. Conceptualizarea lingvistică a prepoziției spațiale românești „în” și a celei polone „w” – abordare comparativă. Prepoziției române „în” îi corespunde prepoziția poloneză „w”. Ambele exprimă relația spațială care constă în plasarea unui obiect într-un spațiu limitat, indicând interiorul spațiului unde se află ceva. Pe lângă această definiție generală, în ambele limbi prepoziția capătă și alte funcții semantice care pot fi convergente, redate direct de perechea rom. în = pol. w. Pe de altă parte, reprezentarea unor relații lingvistice poate fi diferită: ceea ce, pentru un vorbitor român, reprezintă spațiul închis – în, pentru un vorbitor polonez, reflectă spațiul deschis sau o suprafață – na. Obiectivul principal al acestui articol este de a analiza diferențele care rezultă, în primul rând, din diferita conceptualizare a spațiului, reflectată în limbă cu ajutorul prepozițiilor, şi, în al doilea rând, din distincțiile sistemelor gramaticale (roman vs. slav). Analiza este bazată, între altele, pe greșelile frecvente în folosirea structurilor prepoziționale pe care le fac vorbitorii limbii polone învățând româna. Structurile greșite apar mai ales la nivelul limbajului abstract, în sintagme sau la verbe, când regimul acestora impune prepoziții sau cazuri gramaticale care nu corespund funcțional cu cele din limba maternă. În plus, imaginea lingvistică a spațiului este și diferită, și greu de identificat în aceste structuri metaforice (abstracte). Abordarea cognitivă permite delimitarea unor scheme imaginare, care indică sensul primordial al prepoziției. Studierea comparativă a prepoziției în limbile română și polonă arată că sistemul prepozițional în limba română este mai dezvoltat și bogat decât cel polonez, iar acesta din urmă prezintă o atașare mult mai puternică și mai textuală (ad litteram) la trăsătura de „interioritate” exprimată de prepoziția „w/în” decât limba română. Cuvinte-cheie: prepoziții, RLS (româna ca limba străină), conceptualizare lingvistică, imaginar lingvistic, structuri prepoziționale, limba polonă Article history: Received 8 December 2022; Revised 7 February 2022; Accepted 22 February 2023; Available online 27 March 2023; Available print 31 March 2023.